2012
DOI: 10.11646/zootaxa.3538.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of genus- and species-group names of the false limpets Siphonaria (Mollusca: Gastropoda: Euthyneura)

Abstract: Not since Hubendick’s 1946 Systematic Monograph of the Patelliformia has a comprehensive taxonomic work been com-pleted on the genus of false-limpets Siphonaria, distributed worldwide, except in the northern Atlantic. A checklist of allsupra-specific names associated with Siphonaria is established. A checklist of all species-group names is provided as welland their nomenclatural status is discussed (available, not available, permanently invalid). Of the 270 species-group namesincluded in the checklist, 205 are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Together with this, they showed that no Siphonaria species was broadly distributed across the Indo‐West Pacific. Three clades were recorded in southern South America: S. lessonii and two sister cryptic species which had previously been considered as S. lateralis (Dayrat et al., ), also known as Kerguelenella lateralis (White & Dayrat, ). These cryptic species showed 6.9% mtDNA divergence (Dayrat et al., ), and were recognized by Güller, Zelaya, and Ituarte () as S. lateralis and the newly described S. fuegiensis .…”
Section: Introductionmentioning
confidence: 99%
“…Together with this, they showed that no Siphonaria species was broadly distributed across the Indo‐West Pacific. Three clades were recorded in southern South America: S. lessonii and two sister cryptic species which had previously been considered as S. lateralis (Dayrat et al., ), also known as Kerguelenella lateralis (White & Dayrat, ). These cryptic species showed 6.9% mtDNA divergence (Dayrat et al., ), and were recognized by Güller, Zelaya, and Ituarte () as S. lateralis and the newly described S. fuegiensis .…”
Section: Introductionmentioning
confidence: 99%